Low Phosphate Puts Auxin in the Root Hairs. (October 2018) - Parry, Geraint
Abstract : The molecular changes that allow plant roots to response to low phosphate levels are poorly understood. A series of three papers investigate this phenomenon and reveal which components of the auxin response are key for transmitting the phosphate signal into changes in root hair phenotypes.